2021
DOI: 10.1136/rapm-2021-102750
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve block anesthesia/analgesia for patients undergoing primary hip and knee arthroplasty: recommendations from the International Consensus on Anesthesia-Related Outcomes after Surgery (ICAROS) group based on a systematic review and meta-analysis of current literature

Abstract: BackgroundEvidence-based international expert consensus regarding the impact of peripheral nerve block (PNB) use in total hip/knee arthroplasty surgery.MethodsA systematic review and meta-analysis: randomized controlled and observational studies investigating the impact of PNB utilization on major complications, including mortality, cardiac, pulmonary, gastrointestinal, renal, thromboembolic, neurologic, infectious, and bleeding complications.Medline, PubMed, Embase, and Cochrane Library including Cochrane Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 138 publications
2
74
0
1
Order By: Relevance
“…A systematic review of the influence of anesthesia and pain management indicated that general anesthesia may be associated with early POCD, with no effect seen beyond 7 days after joint arthroplasty (Zywiel et al, 2014). And a metaanalysis of 122 studies revealed that peripheral nerve block anesthesia/analgesia use for patients undergoing primary hip and knee arthroplasty (compared with no use) was associated with lower odds ratios for cognitive dysfunction (odds ratio 0.30, 95% CI 0.17-0.53/odds ratio 0.52, 95% CI 0.34-0.80) (Memtsoudis et al, 2021). Multimodal anesthesia protocols have not been definitively demonstrated to reduce the incidence of POCD.…”
Section: Risk Factors For Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…A systematic review of the influence of anesthesia and pain management indicated that general anesthesia may be associated with early POCD, with no effect seen beyond 7 days after joint arthroplasty (Zywiel et al, 2014). And a metaanalysis of 122 studies revealed that peripheral nerve block anesthesia/analgesia use for patients undergoing primary hip and knee arthroplasty (compared with no use) was associated with lower odds ratios for cognitive dysfunction (odds ratio 0.30, 95% CI 0.17-0.53/odds ratio 0.52, 95% CI 0.34-0.80) (Memtsoudis et al, 2021). Multimodal anesthesia protocols have not been definitively demonstrated to reduce the incidence of POCD.…”
Section: Risk Factors For Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…Optimal pain management after TKA is therefore essential to improve early mobilization, rehabilitation, and recovery 2. As a key component of effective multimodal analgesia, continuous adductor canal block (ACB) provides postoperative analgesia while preserving quadriceps strength 3…”
Section: Introductionmentioning
confidence: 99%
“…At present, general anesthesia, combined with nerve block anesthesia, has been widely used in clinical practice, especially in THA, and its advantages are many, such as providing effective relief for perioperative pain, controlling and reducing the dosage of opioids, and promoting the rapid recovery of patients ( 13 , 14 ). The iliac fascia is formed by the muscle fascia of the psoas major, iliacus, and pubis muscles, and the iliac fascia space is a potential gap in the anterior iliac fascia and the posterior iliopsoas and iliopsoas fascia ( 15 17 ). The three main nerves originating from the lumbar plexus—the femoral nerve, the lateral femoral cutaneous nerve, and the obturator nerve—run behind the fascia iliacus and are located together in the fascia iliacus space.…”
Section: Discussionmentioning
confidence: 99%
“…Intraspinal anesthesia is also a commonly used anesthesia scheme for THA patients in clinical practice, but the elderly often encounter many problems such as spinal degeneration, ligament calcification, and difficulty in placing the puncture position, which, in turn, increases the difficulty of the puncture condition ( 14 ). With the recent advancement of ultrasound visualization technology, nerve block technology is being increasingly used for surgical anesthesia and postoperative analgesia in fracture patients ( 15 , 16 ). The advantage of nerve block technology is that it can not only help in good pain management during and after surgery, but also help avoid the impact of general anesthesia on cardiopulmonary function, maintain hemodynamic stability, and reduce the risk of POCD ( 17 ).…”
Section: Introductionmentioning
confidence: 99%